Research on the influencing factors of energy consumption of rural residential buildings in severe cold areas - ZHIYONG, Guo; DZHEDZHULA, Viacheslav (Ways to Improve Construction Efficiency, 2025)
Energy consumption of rural residential buildings was a key issue addressed in global sustainable development efforts. In this study, a typical rural self-built house in the severely cold climate of Jiuquan, China, was selected, and a dynamic energy consumption model was established using DesignBuilder software. The model was used to systematically analyze how six factors – building orientation, storey height, window-to-wall ratio, facade construction, roof construction, and external window materials-affected heating energy consumption through a one-factor experiment and an L25(5^6) orthogonal test. The results revealed that external wall insulation performance played the most significant role in energy consumption regulation, with EPS insulation facades saving 20.4% more energy than traditional clay brick walls. Low-E coated heat-breaking aluminum windows reduced energy consumption by 18.3% compared to single-pane wood frame windows, and using a 100 mm XPS insulation roof saved 9.8% of energy. The sensitivity ranking showed that the thermal parameters of the envelope (facade > windows > roof) had a stronger influence than building form parameters (floor height > window-to-wall ratio > orientation). The optimal combination scheme (WA4+WI5+RO5) achieved an annual energy consumption of 27,707 kWh, a 24.3% reduction from the baseline model. The study proposed a synergistic design strategy prioritizing high-performance envelope retrofits while limiting incremental storey heights and window-to-wall ratios, providing a quantitative basis for locally adapted energy efficiency policies for rural buildings.